Nilai Moral dalam Novel Jangan Salahkan Aku SelingkuhKarya Renita April - Rahmaizar; Fikri, Hasnul; Syofiani, Syofiani (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The title of this research is Moral Values ​​in the Novel Jangan Blame Aku Selingkuh by Renita April. The main objective of the research is to explain the moral values ​​contained in the Novel Jangan Blame Aku Selingkuh written by Renita April. and The theories used in this research include theories from Nurgiyantoro (2012), Wicaksomo (2017), Aeni (2018). The methodology applied in this research is a descriptive method with data sources from the novel Jangan Blame Aku Selingkuh by Renita April. Data collection techniques used in this research include library study techniques, recording techniques, and analysis techniques. The conclusion of the research on moral values ​​in the novel Don't Blame Me for Cheating by Renita April is as follows: (1) The relationship between individuals and themselves includes a) responsibility, b) self-esteem, c) courage, d) emotional control, e) honesty, f) patience and steadfastness, h) regret and i) injustice. (2) The relationship between individuals and others in a social context consists of a) helping each other, b) respecting others, c) affection, d) friendship, e) humility, f) honesty, g) caring, h) empathy, i) loyalty. (3) The relationship between individuals and God includes a) gratitude, b) surrender and c) obedience to God.